Study on the preparation of GeoWEPP model input data for erosion prediction in Cikeruh-Citarik sub-watershed - Amaru, Kharistya; Dwiratna, Sophia; Kendarto, Dwi Rustam; Shofia, Qorry (Universitas Muhammadiyah Mataram, 2022)
Cikeruh-Citarik sub-watershed is a part of the upstream zone of the Citarum watershed which is classified as a watershed with critical conditions in West Java. The change in land use as a side effect of the increasing population causes a degradation of the watershed. Land-use change in a watershed without considering any conservation rules leads to erosion, becoming a watershed criticality indicator. Erosion can be minimized by using a prediction model to predict the amount of erosion that might happen, for the result could help to decide which conservation action is needed in the watershed rehabilitation. GeoWEPP is one of the prediction models that is suitable for predicting the amount of erosion on a watershed scale. This research aims to study the preparation of the input data needed in the GeoWEPP model to predict the amount of erosion, especially in the Cikeruh-Citarik sub-watershed. The methodologies that were used in this research are literature study and field survey. According to the research results, the input data needed for GeoWEPP are DEM (Digital Elevation Model) data of the research area, climate database, soil type and soil physical properties database, land use and landcover data, and bridge files for soil, land cover data, and evapotranspiration calculation.